Peran Neuroprotektif Cognitive Reserve Dalam Menghambat Progresivitas Gangguan Kognitif Terkait Diabetes Melitus Tipe 2 - Harahap, Herpan Syafii; Indrayana, Yanna (Faculty of Medicine Universitas Mataram, 2020)
Cognitive impairment is one of the important complications of type 2 diabetes mellitus. Type 2 diabetes mellitus-associated cognitive impairment has wide spectrum, ranging from mild cognitive impairment to dementia. The susceptibility of patients with type 2 diabetes mellitus to experiencing cognitive impairment is also determined by their previous cognitive reserve status. A good cognitive reserve of a patient with type 2 diabetes mellitus will protect him from cognitive impairment. The components of cognitive reserve, including education, occupation, hobbies, and social and physical activities provide a protective effect through neural reserve and neural compensation mechanisms that lead to a serial processes of neurogenesis, production of neurotropic factors, and neurotransmitter regulation. An understanding of the neuroprotective effects of the components of cognitive reserve is very important in determining optimal cognitive impairment management strategies in type 2 diabetes mellitus patients, in such a way that they are still able to carry out daily functional activities properly.